GAMBARAN SKOR KARIES MENURUT STATUS KEHAMILAN DI PUSKESMAS BAYAT KABUPATEN KLATEN - Anisah Nur Aini; Henry Setyawan Susanto; Sri Yuliawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Increasing the incidence of dental caries is a health problem in Indonesia. Based on Riskesdas 2013, caries patients in the women group (70.7%) were higher than the men group (64.8%). Pregnancy is one cause of high dental caries in the group of women. This is caused by physiological and hormonal changes during pregnancy. The prevalence of dental caries in pregnant women in developing countries as much as 60-87%. The purpose of this research to describe differences in a score caries between nonpregnant women and pregnant women at the Bayat Health Center. This research is descriptive research with Cross sectional approach. The population of this study were all women who examined the teeth and mouth in April 2018 with the age of 20-35 years. The sample is taken as many as 50 pregnant women and 50 non-pregnant women was selected based on the consecutive sampling method. Assessment of dental caries using DMF-T index. Data analysis using frequency distribution and Crosstab. The results showed that non-pregnant women had decay teeth (56%) more than non-pregnant women. Pregnant women have missing teeth (18%) more than non-pregnant women. However, pregnant women have a filling tooth (36%) more than non-pregnant women. Pregnant women have higher dental caries more than non-pregnant women (20%). The advice that can be given to pregnant women is expected by pregnant women to keep more dental hygiene and mouth by reducing sweet foods and more often to clean teeth.